Public health and prevention research within the Medical Research Future Fund - Benedicta Natalia Latif; Leanne Coombe; Tim Driscoll; Anita van Zwieten; Catherine Sherrington; Saman Khalatbari-Soltani (Elsevier, 2024)
Objective: To explore the amount and type of research funded under relevant Medical Research Future Fund (MRFF) Initiatives that addressed public health and prevention from 2018 to July 2023. Methods: Projects funded by six MRFF Initiatives, with objectives relevant to public health and public health nominated as "field of research" by >25% of applicants, were evaluated against a set of public health research criteria and were categorised based on levels of prevention. Results: Fifty-seven per cent of 249 funded projects were categorised as public health research. Projects with curative features, focusing on tertiary (32%) and quaternary (4%) prevention, were as common as projects with earlier preventive features, focussed on primordial (7%) and primary (28%) prevention. The Preventive and Public Health Research Initiative had the lowest proportion of public health research (48%) of the six evaluated Initiatives and a dominance of curative (39%) and non-preventive (26%) research over preventive research (30%). Conclusion: This study highlighted variable levels of public health research across public-health-relevant MRFF Initiatives and generally low proportions of primary and primordial prevention. A greater emphasis on primordial and primary prevention research in public-health-relevant Initiatives could advance prevention in Australia. Implications for public health: There appears to be scope for improvement in the prioritisation of upstream prevention research in public-health-relevant MRFF Initiatives and projects. Addressing this may enhance the benefit of MRFF to Australian public health.